PERBANDINGAN AKTIVITAS DAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN SOMATIS AUDITORI VISUAL INTELEKTUAL (SAVI) BERBANTUAN BAHAN AJAR BERBASIS ANDROID DENGAN PRAKTIKUM - Kartika Wahyuni; Amir, Hermansyah; Sura Menda Ginting (University of Bengkulu, 2024)
This study aims to determine the differences in the activities and learning outcomes of students who apply the somatic, auditory, visual, intellectual (SAVI) learning model assisted by android-based teaching materials and practicum. This study uses a quasi-method with research samples of experimental class I used android-based teaching materials and experimental class II applying practicum. The method of data collection was carried out by conducting tests in measuring learning outcomes while the observation sheet of student activities in measuring learning activities. The results of observing the learning activities of students in the experimental class 1 and 2, respectively, are 69% and 74%, both in the active criteria. The cognitive learning outcomes of experimental class 1 and 2 students are 75.76 and 79.61, both in good criteria. There is a significant difference between learning activities and student learning outcomes who are taught by the application of the SAVI learning model assisted by android-based teaching materials and practicum. The results of the study can be concluded that in general the activities and learning outcomes of students with the application of the SAVI learning model with practicum are higher than those with the help of android-based teaching materials.